Effect of Character Marketing and Marketing Mix on Usage Intention of Internet-Only Banks: Evidence From South Korea. (December 2021) - Lee, Jong Ho; Park, Heejun
Two South Korean internet-only banks were established around the same time, but their performances differ significantly when the product is similar to intangible values such as brand equity and marketing efforts. This study credits brand equity with causing performance difference and proposes a research model to examine which marketing activities construct brand equity. Traditional 4P marketing activities and character marketing are selected as marketing mix activities. Additionally, this research examines whether marketing activity effectiveness is affected by gender and evaluates customer perception about internet-only banking based on a survey. The results show that all the considered marketing activities are significant in establishing brand equity; however, their effect on brand equity is moderated by gender. This research contributes to marketing by considering brand equity in the internet-only banking context and emphasizing the effect of marketing activities using characters. Industry managers could use these results to achieve competitiveness by fostering brand equity.